DAMPAK AKTIVITAS MASYARAKAT TERHADAP KUALITAS AIR SUNGAI BABARSARI KECAMATAN KUTALIMBARU KABUPATEN DELI SERDANG - Elisa Lestari Simanjuntak; Pindi Patana; Rusdi Leidonald (AQUACOASTMARINE, 2017)
River is one of the water source which is very important for people because it can serve as a source of drinking water, and environmental sevices also as tourist attractions. This research was conducted on May-June 2017 at Babarsari River Kutalimbaru District of Deli Serdang Regency, it’s to analyz the influence of community activity on water quality of Babarsari river and to describe perception of visitor and manager on Babarsari tourism. The parameters observed were temperature, brightness, flow Rate, DO, pH, BOD5, N, P and total coliform. The results showed that according to Government Regulation No. 82/2001 and STORET rating system at stations 1 and 2 it categorized in class A (Very good) by fulfilling the Quality Standard, while Station 3 and 4 werecontaminated in medium condition with scores of -25 and -17. Perception of visitors to Babarsari tourism amounted to 75.6% stated Comfort and beauty level of 79.1% entered in the beautiful category. There are 5 managers or 100% who handle the garbage by stacked and then burned, there is a ban for visitors littering in order to maintain cleanliness of the area.Kata kunci : water quality, human activities, quality standart, Babarsari rivers